Tripotential differentiation of adherently expandable neural stem (NS) cells. - Tamara Glaser; Steven M Pollard; Austin Smith; Oliver Brüstle (PLoS ONE)
Background A recent study has shown that pure neural stem cells can be derived from embryonic stem (ES) cells and primary brain tissue. In the presence of fibroblast growth factor 2 (FGF2) and epidermal growth factor (EGF), this population can be continuously expanded in adherent conditions. In analogy to continuously self-renewing ES cells, these cells were termed 'NS' cells (Conti et al., PLoS Biol 3: e283, 2005). While NS cells have been shown to readily generate neurons and astrocytes, their differentiation into oligodendrocytes has remained enigmatic, raising concerns as to whether they truly represent tripotential neural stem cells. Methodology/principal findings Here we provide evidence that NS cells are indeed tripotent. Upon proliferation with FGF2, platelet-derived growth factor (PDGF) and forskolin, followed by differentiation in the presence of thyroid hormone (T3) and ascorbic acid NS cells efficiently generate oligodendrocytes ( approximately 20%) alongside astrocytes ( approximately 40%) and neurons ( approximately 10%). Mature oligodendroglial differentiation was confirmed by transplantation data showing that NS cell-derived oligodendrocytes ensheath host axons in the brain of myelin-deficient rats. Conclusions/significance In addition to delineating NS cells as a potential donor source for myelin repair, our data strongly support the view that these adherently expandable cells represent bona fide tripotential neural stem cells.